МІСЬКА VS РЕГІОНАЛЬНА ІДЕНТИЧНІСТЬ: ДО ПИТАННЯ ХАРАКТЕРУ ФОРМУВАННЯ/АКТУАЛІЗАЦІЇ/ПРОТИСТАВЛЕННЯ В УМОВАХ СУЧАСНОГО УКРАЇНСЬКОГО СУСПІЛЬСТВА - Міхно Надія Костянтинівна (International Journal of Innovative Technologies in Social Science, 2020)
The main focus of this article is on identifying the features of regional and urban identity formation and actualization. An attempt was made to determine the nature of interaction and juxtaposition of these types of territorial identity in the conditions of modern Ukrainian society. The main mechanisms of formation of regional identity are distinguished: use of the mechanism of constructing crisis or opposition regional identity, ideological work as a mechanism of formation of regional identity, images, symbolism, mythologists, ideologists and communication slogans as mechanisms of formation of regional identity. Urban identity is formed during the symbolic production of urban meanings. It is emphasized that urban identity is a socio-cultural construct, which is formed as a result of socialization and adaptation in a certain settlement and is determined by the assimilation and reproduction of cultural symbols, accepted norms, traditions, lifestyle of the city residents. It is determined that in modern Ukrainian society urban identity prevails over regional identity.